Social movements and organization theory - Davis, Gerald F. (Gerald Fredrick), 1961- (Cambridge studies in contentious politics., 2005)
"Organization theory and social movement theory are two of the most vibrant areas within the social sciences. This collection of original essays and studies both calls for a closer connection between these fields and demonstrates the value of this interchange. Two introductory, programmatic essays by leading scholars in the two fields are followed by nine studies that directly illustrate the benefits of this type of cross-pollination and two closing essays. The studies variously examine the processes by which movements become organized and the role of movement processes within and among organizations. The topics covered range from globalization and transnational social movement organizations to community recycling programs."--Jacket